Persistent adaptation through dual-timescale regulation of ion channel properties - Yugarshi Mondal; Ronald L. Calabrese; Eve Marder (Proceedings of the National Academy of Sciences, 2026)
Neurons are terminally differentiated cells that adapt to maintain stable function over years, despite encountering a wide range of environmental perturbations. In some cases, recovery from perturbation is not shaped by prior exposure; in others, recovery depends on the neuron’s perturbation history. A particularly striking form of history-dependent recovery occurs when prior exposure enhances the neuron’s ability to recover from future perturbations while leaving baseline activity largely unchanged. Among the many mechanisms that may contribute to such history-dependent improvement in recovery, we investigate one based on the regulation of intrinsic currents. Using a model of activity-dependent homeostasis, we show that improved recovery can be encoded through lasting changes in channel density, while rapid shifts in ion channel voltage-dependence provide immediate compensation during perturbations. We refer to the long-lasting intrinsic trace that accompanies this improved recovery a persistent adaptation. Interestingly, these roles are noninterchangeable: when voltage-dependence evolves slowly and maximal conductances change rapidly, an intrinsic trace is not stored, eliminating persistent adaptation even when improved recovery is preserved.